Activation of canonical Wnt signalling is required for TGF-β-mediated fibrosis - Akhmetshina, Alfiya; Palumbo, Katrin; Dees, Clara; Bergmann, Christina; Venalis, Paulius; Zerr, Pawel; Horn, Angelika; Kireva, Trayana; Beyer, Christian; Zwerina, Jochen; Schneider, Holm; Sadowski, Anika; et al. (Nature Communications, 2012)
The transforming growth factor-β (TGF-β) signalling pathway is a key mediator of fibroblast activation that drives the aberrant synthesis of extracellular matrix in fibrotic diseases. Here we demonstrate a novel link between transforming growth factor-β and the canonical Wnt pathway. TGF-β stimulates canonical Wnt signalling in a p38-dependent manner by decreasing the expression of the Wnt antagonist Dickkopf-1. Tissue samples from human fibrotic diseases show enhanced expression of Wnt proteins and decreased expression of Dickkopf-1. Activation of the canonical Wnt pathway stimulates fibroblasts in vitro and induces fibrosis in vivo. Transgenic overexpression of Dickkopf-1 ameliorates skin fibrosis induced by constitutively active TGF-β receptor type I signalling and also prevents fibrosis in other TGF-β-dependent animal models. These findings demonstrate that canonical Wnt signalling is necessary for TGF-β-mediated fibrosis and highlight a key role for the interaction of both pathways in the pathogenesis of fibrotic diseases. © 2012 Macmillan Publishers Limited. All rights reserved.
CRIS-Team Scopus Importer:2020-07-01